Association between MTHFR gene C677T polymorphism and gestational diabetes mellitus in Chinese population: a meta-analysis - Tan, Xi; Chen, Hongqin (Frontiers in Endocrinology, 2023)
Background and purpose The relationship of the methylenetetrahydrofolate reductase (MTHFR) gene C677T polymorphism with the incidence of gestational diabetes mellitus (GDM) in the Chinese population remains controversial. This study aimed to further clarify the effect of the MTHFR gene C677T polymorphism on GDM risk among Chinese pregnant women based on current evidence. Methods Several databases were searched up to July 29, 2023 for relevant case‒controlcase-control studies. NumbersThe numbers of patients with and without the T allele of the MTHFR gene C677T polymorphism in the GDM and control groups were collecteddetermined, and all statistical analysis wasanalyses were performed by RevMan 5.3 software and STATA 15.0 software. Trial sequential analysis (TSA) was performed by TSA version 0.9 beta software to determine the required information size. Results A total of 17 case‒controlcase-control studies involving 12345 Chinese participants were included. The pooled results demonstrated that the T allele of the MTHFR gene C677T polymorphism was significantly associated with an increased risk of GDM, which was manifested by the five gene models of the MTHFR C677T polymorphism [T vs.vs C: odds ratio (OR)=1.59, P=0.03; TT vs.vs CC: OR=2.24, P＜0.001; TC vs.vs CC: OR=1.28, P=0.05; (TT+TC) vs.vs CC: OR=1.55, P=0.003; TT vs.vs (TC+CC): OR=1.89, P＜0.001]. Subgroup analysis based on the regions indicated that the significant relationship between the T allele of the MTHFR gene C677T polymorphism and an increased risk of GDM was detected onlywas only detected among the southern population [T vs.vs C: OR=1.62, P=0.09; TT vs.vs CC: OR=2.22, P=0.004; TC vs.vs CC: OR=1.17, P=0.28; (TT+TC) vs.vs CC: OR=1.43, P=0.03; TT vs.vs (TC+CC): OR=1.97, P=0.006]. TSA plots manifestedshowed that the information sizes for the association between the MTHFR gene C677T polymorphism and GDM risk were sufficient under in the homozygote (TT VSvs. CC) and recessive (TT VSvs. TC+CC) models.